Social communication between social workers and media: transparency, trust, and digital adaptation - Mikheieva, Oksana; Synytsia, Anton (Interacción y Perspectiva, 2025)
Communication between social workers and media representatives plays a crucial role in shaping public opinion by promoting informational transparency and strengthening trust in social institutions. In the current context of digitalization and the expansion of information technologies, this interaction is undergoing profound transformations that require a thorough analysis of emerging trends and the most effective approaches for designing communication strategies. This article examines prevailing models of social communication and defines optimal strategies to enhance interaction between these two actors. The methodology is based on theoretical analysis, comparative methods, and content analysis of scientific sources, allowing for the identification of current challenges and the evaluation of dominant approaches in communication processes. Findings reveal that the effectiveness of social communication depends on the media literacy of social workers, their ability to adapt traditional methods to digital environments, and the implementation of long-term sustainable strategies. Key factors for improving the quality of engagement with the media include the stra- tegic use of social networks, the creation of integrated information platforms, and specialized training programs. However, several barriers persist, such as low public trust in social services, bureaucratic constraints, and the media’s tendency toward sensationalism. The practical relevance of the study lies in the develop- ment of recommendations for social institutions to strengthen their communication strategies, thereby enhancing their efficiency, ensuring transparency, and fostering a positive image of the social sector.